Dramaturgical Design Based on The Legend of Dideng Puti Dayang Ayu from Rantau Pandan - Irianto, Ikhsan Satria; M., Hartati; Riswani; Gustyawan, Tofan (Mudra Jurnal Seni Budaya, 2024)
Dideng is an oral art from Rantau Pandan Village whose existence is of concern due to the lack of regeneration. In fact, Dideng art has theatrical, musical and gestural power. The content of Dideng is the legend of Puti Dayang Ayu which has great dramatic potential. Designing a performance concept (dramaturgical design) based on the legend of Puti Dayang Ayu is an effort to revitalize and develop Jambi's dramatic arts. This research aims to find dramatic material to then reassemble into a dramaturgical plan based on the legend of Dideng Puti Dayang Ayu. This research uses a qualitative method with a case study approach. The data collection techniques used were interviews and observation. Data analysis was carried out using three analytical tools, namely data reduction, data presentation, and drawing conclusions. The results achieved from this research are 1). Dideng is a means of entertainment for the people of Rantau Pandan village which does not yet have a good regeneration of speakers. Therefore, creativity is needed to create Dideng in more attractive packaging. 2). The Dideng text was passed down orally so it does not have a standard story. Each speaker has their own version of the story. Therefore, the preparation of the story is adjusted to the dramatic needs of the story. 3). The writing of this play was motivated by the dramatic vision of "rationalization of legend". The main theme is broken promises and is structured in an aristolelian episodic plot.